2010
DOI: 10.4314/swj.v1i1.51691
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of some species of mosquitoes to permethrin pyrethroid in Zaria Nigeria.

Abstract: The susceptibility of Aedes aegypti Linnaeus 1762, Culex quinquefasciatus Say 1823 and Anopheles gambiae Giles 1902 was tested on 0.75 % permethrin pyrethroid in the laboratory. All Larval and pupal stages of the mosquitoes were collected from different localities within Zaria, Nigeria and reared to adulthood in the laboratory. The adults that emerged were tested on 0.75 % permethrin strips using WHO Standard Test Kit. Mortalities were recorded at five minutes interval for 1 hr and maintained for 24hrs post-ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 7 publications
(4 reference statements)
1
8
0
Order By: Relevance
“…Previous studies have also reported susceptibility of Ae. a egypti to permethrin in urban areas of Nigeria and Senegal ( Ndam et al. 2006 ; Dia et al.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also reported susceptibility of Ae. a egypti to permethrin in urban areas of Nigeria and Senegal ( Ndam et al. 2006 ; Dia et al.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is imperative to periodically conduct bioassays tests to assess the susceptibility status of local mosquito species to IRS interventional insecticides. The susceptibility of Anopheles mosquitoes against insecticides was fairly evaluated in southern parts of Nigeria (Olayemi et al, 2011;Oduola et al, 2012) but there was dearth of information in the northern Nigeria (Molta and Ali, 1998;Ndams et al, 2006). No documented evidence on the susceptibility status of Anopheles mosquitoes to guide procurement of IRS insecticide in Northeast Nigeria is available.…”
Section: Introductionmentioning
confidence: 99%
“…The major challenge in use of these insecticides in malarial vector control has been the development of resistance to insecticides among the vector populations. Anopheles mosquitoes resistance to insecticides is spreading rapidly across African countries (Awolola et al, 2002(Awolola et al, , 2005(Awolola et al, , 2007Ndams et al, 2006;Oduola et al, 2010;Ranson et al, 2011;Kabula et al, 2012;Natacha et al, 2013;Ibrahim et al, 2014) and could reduce the impact of malaria prevention interventions using IRS and LLINs, particularly in sub-Sahara Africa (NGuessan et al, 2007;Awolola et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In South West Nigeria, the first case of pyrethroid resistance in Anopheles gambiae, a major malaria vector, in Nigeria was documented by Awolola et al (2002) and since then the occurrence has been well established in this region (Kristan et al 2003;Oduola et al 2010). In North-central Nigeria, permethrin and DDT resistance in Anopheles gambiae has also been reported (Ndams et al 2006;Olayemi et al 2011). Thus, synthetic insecticides have caused several problems including the development of resistant insect strains, ecological imbalance, harm to mammals, and non-target arthropods.…”
Section: Introductionmentioning
confidence: 88%